Developing national and local innovation platforms in the NIle BDC - group feedback - Swaans, Cornelis P.M. (International Livestock Research Institute, 2011)
In early May 2011, people working on the Nile Basin Development Challenge (http://nilebdc.org) met in Addis Ababa in a 'science and reflection workshop'. Session 2 of the workshop examined institutional and other processes that are key to success of the overall program. In this video, Kees Swaans (ILRI) reports from small group discussions on issues related to the establishment of 'innovation platforms'—what we envisage for national and local platforms.